Hambatan Kearifan Lokal Anyaman Bambu Sebagai Potensi Ekonomi Kreatif Bagi Perempuan Di Desa Suka Maju - Benedhikta Kikky Vuspitasari; Shanti Veronica Br Siahaan (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2022)
This article aims to describe the barriers to local wisdom of woven bamboo as creative economic potential for women in Suka Maju Village. This research is a qualitative descriptive study using purposive sampling method, data collection, researchers using interviews, observations, and documents. The data analysis used in this study consisted of several stages, namely data reduction, data presentation, and drawing conclusions, to determine the validity of the researcher's data using data triangulation techniques. The results of the study found that the obstacles to local wisdom of woven bamboo as potential for the creative economy were the lack of product innovation, traditional product marketing and a lack of business networks.